Control of the Rhizobia Nitrogen-Fixing Symbiosis by Common Bean MADS-Domain/AGL Transcription Factors - Ayra, Litzy; Reyero-Saavedra, María del Rocio; Isidra-Arellano, Mariel C.; Lozano, Luis; Ramírez, Mario; Leija, Alfonso; Fuentes, Sara-Isabel; Girard, Lourdes; Valdés-López, Oswaldo; Hernández, Georgina (Frontiers in Plant Science, 2021)
Plants MADS-domain /AGL proteins constitute a large transcription factor (TF) family that control the development of almost every plant organ. We performed a phylogeny of (ca. 500) MADS-domain proteins from Arabidopsis and four legume species. We identified clades with Arabidopsis MADS-domain proteins known to participate in root development that grouped legume MADS-proteins with similar high expression in roots and also in nodules. In this work we analyzed the role of AGL transcription factors in the common bean (Phaseolus vulgaris) – Rhizobium etli N-fixing symbiosis. Sixteen P. vulgaris AGL genes (PvAGL), out of 93 family members, are expressed -at different levels- in roots and nodules. From these we selected the PvAGL gene denominated PvFUL-like for overexpression or silencing in composite plants, with transgenic roots and nodules, that were used for phenotypic analysis upon inoculation with Rhizobium etli. Because of sequence identity in the DNA sequence used for RNAi-FUL-like construct, roots and nodules expressing this construct -referred to as RNAi_AGL- showed lower expression of other five PvAGL genes highly expressed in roots/nodules. Contrasting with PvFUL-like overexpressing plants, rhizobia-inoculated plants expressing the RNAi_AGL silencing construct presented affection in the generation and growth of transgenic roots from composite plants, both under non-inoculated or rhizobia-inoculated condition. The rhizobia-inoculated plants showed decreased rhizobial infection concomitant with lower expression level of early symbiotic genes, and increased number of small, ineffective nodules that indicate an alteration in the autoregulation of nodulation symbiotic process. We propose that the positive effects of PvAGL TF in the rhizobia symbiotic processes result from its potential interplay with NIN, the master symbiotic TF regulator, that showed a CArG-box consensus DNA sequence recognized for DNA binding of AGL TF and presented an increased or decreased expression level in roots from non-inoculated plants transformed with RNAi_AGL or OE_FUL construct, respectively. Our work contributes to define novel transcriptional regulators for the common bean - rhizobia N-fixing symbiosis, a relevant process for sustainable agriculture.